2012
DOI: 10.4028/www.scientific.net/msf.721.205
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Behavior of Micrometer-Size Particles in the Polishing Process of a Micro-Tube Filled with a Magnetic Fluid under Uniform Magnetic Field

Abstract: Behavior of suspended magnetic and nonmagnetic micrometer-size particles in a micro-tube filled with a magnetic fluid is investigated by using the discrete particle method based on the simplified Stokesian dynamics in order to know the polishing process of inner wall of a tube. It is shown that the chain-like clusters of magnetic particles are surrounded by clusters of nonmagnetic particles in the presence of uniform magnetic field. The clusters are held in the field direction in case of rotation of the micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the first report, behavior of particles in the fluid in the polishing process of inner wall surface of a circular micro-tube rotating with constant angular velocity under applied non-uniform magnetic field have been examined [12]. In the second paper, the behaviors of micrometer-size particles in the fluid have been studied for two cases: rotating tube and rotating uniform magnetic field [13]. In the latest study, it is shown that applying axial flow of appropriate velocity is effective on improvement of uniform polishing on the inner wall surface in the magnetic compound fluid polishing [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the first report, behavior of particles in the fluid in the polishing process of inner wall surface of a circular micro-tube rotating with constant angular velocity under applied non-uniform magnetic field have been examined [12]. In the second paper, the behaviors of micrometer-size particles in the fluid have been studied for two cases: rotating tube and rotating uniform magnetic field [13]. In the latest study, it is shown that applying axial flow of appropriate velocity is effective on improvement of uniform polishing on the inner wall surface in the magnetic compound fluid polishing [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, polishing mechanism had not been clarified, because it is difficult to visualize the behavior of micrometer-size particles in the process of polishing due to opaqueness of the fluids. In the previous papers [10,11], we have reported behaviors of suspended micrometer-size particles in the process of magnetic compound fluid polishing of the inner surface of a circular micro-tube when the applied magnetic field rotates or the micro-tube rotates with constant angular velocity. In these cases, both magnetic particles and nonmagnetic abrasive particles form chain-like clusters and combined each other, and then form sheet-like structure state leading to non-uniform polishing on the inner surface of the tube in the final state.…”
Section: Introductionmentioning
confidence: 99%